Structural changes in perylene from UV Raman spectroscopy up to 1 GPa. (8th February 2016) - Montagnac, G.; Cardon, H.; Daniel, I.; Reynard, B.
Abstract : Vibrational properties and structural changes under pressure of a highly luminescent molecular organic crystal have been investigated by ultraviolet resonant Raman spectroscopy with a 244‐nm excitation. Resonant Raman modes of α ‐perylene crystal up to 1GPa were followed under hydrostatic pressure in an anvil cell with a sapphire window transparent to ultraviolet light. Nonlinear evolution of intra‐molecular modes is induced by pressure. Abrupt shifts of Raman wavenumbers suggest structural and planar modifications of the molecules in the crystal. We interpret these shifts as a first‐order phase transition to a lower volume of unit cell. The luminescence of perylene crystal is gradually modified as a consequence of these structural changes. The present experimental setup allows investigating with Raman spectroscopy very luminescent molecules involved in chemical reactions and molecular organic crystals under relatively high pressure (up to 1GPa). Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Vibrational properties and structural changes under pressure of α ‐perylene crystal have been investigated in situ by ultraviolet resonant Raman spectroscopy with a 244‐nm excitation. Our results suggest a pressure‐induced phase transition of the crystal. This present setup combines ultraviolet Raman spectroscopy and luminescence emission to open up a new domain of study of highly luminescent molecules involved in chemical reactions and molecular organic crystals under relatively high pressure (up to 1 GPa).